Enhancing Cr(VI) bioreduction via Na+-stimulated intracellular energy metabolism and electron transfer using methane as electron donor - Lianfu Liang; Xiaofeng Fu; Yuqing Ding; Keying Liu; Rui Lin; Zhaojin Chen (Bioresource Technology, 2027)

Biochar enhances anaerobic oxidation of methane coupled with Cr(VI) reduction: Pyrolysis temperature-dependent electron transfer pathways and regulatory mechanisms - Lianfu Liang; Yepu Li; Xiaofeng Fu; Rui Lin; Keying Liu; Zhiqiang Zhao (Bioresource Technology, 2026)

Precise radical quantification and process optimization of UV/persulfate advanced oxidation for sertraline removal - Xiaofeng Zeng; Wenbo Ren; Xitao Liu; Yanwei Zhao; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Journal of Environmental Chemical Engineering, 2026)

A non-complex-algorithmic and manually calculable fragment-resolved isotope framework ratios for geographic authentication of refined sugar - ShuoCong Li; ZhenPeng Zhen; XiaoFeng Xie; RongWei Fu; DeJin Kong; Zhu Lin; ZhaoHua Ping; GuiHua Wang; YuFeng Gao (Food Chemistry, 2026)

Overexpression of DR1372 gene from Deinococcus radiodurans improves the salt and drought tolerance in soybean - Lili Zhou; Ke Zang; Xinyan Liu; Peilin Wang; Wenfang Guo; Xiaofeng Su; Mahideen Afridi; Jin Wang; Min Lin; Hongmei Cheng; Huiming Guo (Plant and Soil, 2026)

Melatonin remodels gut microbiota and tryptophan metabolism to ameliorate methamphetamine-induced cognitive impairment - Lin Miao; Lisha Xu; Xue Yang; Yingjie Zhao; Qiaoqiao Liu; Xiaoxuan Zheng; Xinyu Zheng; Liu Liu; Jian Huang; Juan Li; Xiaofeng Zeng (Journal of Hazardous Materials, 2026)

Mantle melting and magma ocean dynamics on Mercury impacted by sulfur in reduced mafic magmas - Xiaofeng Lu; Olivier Namur; Yongjiang Xu; Bernard Charlier; Yanhao Lin (Earth and Planetary Science Letters, 2026)

Simulated freeze–thaw cycles restructure plastisphere microbiomes and functional gene co-occurrence networks in alpine lake sediment microcosms - Li Naying; Zhong Bo; Wu Wei-Min; Liu Xin; Liu Ruixi; Mei Xintong; Wang Xiaofeng; Zhou Li; Yi Shaoliang; Lin Honghui; He Yixin (Environmental Pollution, 2026)

Sulfur-Oxidizing Bacteria Dominate Soil Microbial Interactions in Chinese Coastal Wetlands - Lun Wang; Kexin Zhang; Jiqiu Li; Xiaofeng Lin (Journal of Ocean University of China, 2026)

The influence of perforation stimulation for natural gas hydrates reservoir on seafloor stability - Lin Yang; Qianyong Liang; Xuhui Zhang; Yudong Huang; Xuemin Wu; Xiaofeng Dou; Zhigang Wang (Ocean Engineering, 2026)

Targeted metabolomics analysis for discriminating geographical origin of Chardonnay grape and wine at sub-regions in China's Ningxia: Terroir effect - Xiaofeng Yue; Yang Zhang; Xinran Bai; Bo-chen Liu; Yu-lin Fang; Yan-lun Ju (Food Research International, 2026)

Sonar-Based Seepage Detection and Hydro-Thermal Modelling of Frozen Soil Curtain Evolution for Subway Cross-Passages in High-Permeability Strata - Shengbin Hu; Hang Lin; Jun Hu; Bafeng Ren; Xiaofeng Song; Zhuang Hu; Hanyu Dang (Geotechnical and Geological Engineering, 2026)

Integrating environmental DNA and trawl surveys to assess seasonal dynamics of fish communities in the Oujiang River Estuary - Chen Weifeng; Ruan Huiting; Wang Wei; Xu Kaiping; Peng Xin; Zhu Rong; Lu Yumiao; Ye Shen; Lin Hungdu; Wang Chen; Zhou Xiaofeng (Frontiers in Marine Science, 2026)
Introduction Monitoring of estuarine fish biodiversity is often constrained by the inherent limitations of traditional survey methods and the complex, dynamic environmental conditions of estuarine habitats. Environmental DNA (eDNA) metabarcoding has emerged as a robust molecular tool for aquatic biodiversity assessment. Nevertheless, its complementary potential to conventional bottom trawling remains understudied in estuarine ecosystems. In this study, we integrated eDNA metabarcoding and bottom trawling to investigate the spatiotemporal dynamics of fish diversity in the Oujiang River Estuary (ORE). Methods Fish assemblage data were collected seasonally across four sampling periods at five fixed sites within the ORE. MiFish-U primers targeting the 12S rRNA gene were utilized for eDNA amplification. And twelve aquatic environmental variables were quantified to disentangle correlations between fish community structure and ambient environmental conditions. Multiple statistical approaches, including alpha diversity analysis, Principal Coordinate Analysis (PCoA) and PERMANOVA, were applied to quantify spatiotemporal shifts in fish assemblages, identify fish-environment correlations, and compare community discrepancies between the two survey methods. Results and discussion The combined approach detected a total of 100 fish species across 84 genera and 45 families. Specifically, eDNA metabarcoding identified 72 fish species, while bottom trawling captured 48 species, with only 20 species shared between the two methods. Fish assemblages exhibited distinct seasonal variations, with both survey methods revealing higher species richness during wet seasons. Temporal fluctuations in water temperature, dissolved oxygen, salinity and nutrient concentrations constituted the primary environmental drivers structuring estuarine fish assemblages, whereas spatial heterogeneity across sampling sites exerted no statistically significant influence on community composition. eDNA metabarcoding showed unique advantages in detecting pelagic, migratory, cryptic and endangered fish species, supporting effective biodiversity monitoring in topographically intricate estuarine waters. In contrast, bottom trawling provided reliable morphological identification and quantitative abundance data for demersal fish taxa, which helped resolve ambiguous species annotations derived from eDNA sequencing. In addition, seven IUCN-listed threatened fish species were documented during the field investigation. Collectively, our findings demonstrate that eDNA metabarcoding and bottom trawling serve as highly complementary, rather than mutually exclusive, tools for fish biodiversity assessment. The integration of the two methods enables a more comprehensive and accurate evaluation of estuarine fish diversity. This study validates the feasibility and efficacy of the combined monitoring framework for macrotidal estuaries and provides valuable scientific references for the ecological conservation and management of the Oujiang River Estuary as well as other similar coastal ecosystems.

Wind direction variability and simplified modeling of multiple hazardous extreme wind events from field measurements - Shihan Wang; Yejun Ding; Xiaofeng He; Lin Zhao (Building and Environment, 2026)

Elucidating β-ocimene ozonolysis through combined experiments and theoretical calculations: The Criegee intermediate and peroxy radical pathways - Yu Xia; Xiaofeng Tang; Xiaoxiao Lin; Bo Long; Christa Fittschen; Weijun Zhang (Atmospheric Environment, 2026)

Taxonomy and Phylogeny of the Little-Known Ciliate Genus Cyclotrichium: With Special Reference to Two New Species - Zijun Cheng; Bowen Ye; Gang Li; Xiping Lian; Yehui Tan; Xiaofeng Lin; Weiwei Liu (Journal of Ocean University of China, 2026)

Effects of predation risk intensity on the trade-off between benefit and cost of anti-predator responses - Weihuang Chen; Ya Hao; Xiaofeng Lin; Jiqiu Li (Journal of Experimental Marine Biology and Ecology, 2026)

Microplastic pollution enhances methane emissions from remote mountainous lakes via plastisphere-mediated microbial processes - Naying Li; Bo Zhong; Wei-Min Wu; Xintong Mei; Ruixi Liu; Xin Liu; Xianxiang Li; Rehman Abdul; Shaoliang Yi; Li Zhou; Honghui Lin; Xiaofeng Wang; et al. (Journal of Environmental Sciences, 2026)

A novel double-layer composite material with excellent radiative cooling and thermal management for electronic devices - Haoxin Lv; Haixuan Liu; Jiahui Lin; Jintao Huang; Hanlin Xie; Xiaofeng Li; Yonggang Min; Xiang Lu (Chemical Engineering Journal, 2026)

Ecotoxicity of ultraviolet radiation on ciliates: Population growth, DNA damage and photooxidative stress - Xuejie Zhang; Chen Chen; Qinyun Zheng; Xiaofeng Lin; Jiqiu Li (European Journal of Protistology, 2026)

Construction of proton affinity environment around Ni-sites to enhanced electrocatalytic carbon‑carbon coupling - Xiaofeng Liu; Ruiji Wang; Fayou Tian; Hao Ren; Jinglin Wang; Yan Lin; Zhongtao Li; Mingbo Wu (Chemical Engineering Journal, 2026)

Physical modulation of starch/non-starch polysaccharide complexes for tailored functional foods: A comprehensive review - Xiangyu Lin; Muhammad Awais; Wenjing Zhu; Husnain Raza; Xiaofeng Ren (Carbohydrate Polymers, 2026)

Global-to-regional variations in the effects of grassland management on soil carbon - Xi Lin; Shengwei Zhang; Alfredo Huete; Han Y.H. Chen; Hongbin Zhao; Qinsi He; Shengwei Lv; Qian Zhang; Xiaoduo Zhang; Xiaofeng Zhang (Agriculture, Ecosystems & Environment, 2026)

Exploring efficient mainstream nitrogen removal by partial nitrification/anammox under limited COD condition in a pilot-scale membrane aerated biofilm reactor - Lisheng Wang; Congcong Zhang; Xiaofeng Kang; Yanchen Liu; Yong Qiu; Deqing Wanyan; Jiayin Liu; Gang Cheng; Pengfei Lin; Xia Huang (Water Research, 2026)

Synergistic effects of multi-frequency ultrasonication on starch-gum interactions for sialorrhea management: Implications for structural, functional, digestibility properties, and molecular docking studies - Muhammad Awais; Wenjiang Dong; Baoguo Xu; Qiufang Liang; Lin Xiangyu; Yufan Sun; Mingming Zhong; Mohamed Ibrahim Younis; Husnain Raza; Ekram Abd El-Salam; Xiaofeng Ren (Food Hydrocolloids, 2026)

Ecological Function Zoning Based on Ecosystem Health Assessment: A Case Study in Qinghai and Xizang, China - Zixu Jia; Xiaofeng Wang; Tao Lin; Wenjie Yao; Jiahao Ma; Jitao Zhou; Xiaoxue Wang; Xinrong Zhang; You Tu; Zechong Sun; Xiaoming Feng; Matthew Kok Ming Ng (Chinese Geographical Science, 2026)

Modulating kinetic regimes in oxidative dehydrogenation of propane via subsurface metal-mediated dynamic BO-H bond dissociation and regeneration - Shiqiang Xu; Ziyu Song; Haotian Zhang; Zepeng Hou; Xian Zhou; Yingjie Yang; Xiaofeng Gao; Lili Lin; Siyu Yao (Chemical Engineering Journal, 2026)

Oriented microstructures and HA/PSP modulation of PEEK implants synergistically promote muscle integration via Myogenesis, immunomodulation and angiogenesis - Yang Su; Yu Chen; Zhengrui Li; Zhaocheng Pan; Lai Jiang; Xiaofeng Xu; Chengshuai Yang; Jinyang Wu; Yong Zhang; Kaili Lin; Shilei Zhang (Chemical Engineering Journal, 2026)

Biochar accelerated soil atrazine degradation by promoting dechlorination pathway: A novel mechanism revealed by DNA stable isotope probing (DNA-SIP) - Guiqiong Yang; Zhen Zhen; Kun Zhang; Junyong Yin; Xiaolan Zhong; Xiaofeng Li; Qing Li; Kaijiang Nie; Xiaoyang Miao; Zhong Lin; Dayi Zhang (Bioresource Technology, 2026)

Contract signing and low-carbon technology adoption in rice production: survey evidence from China - Lin Tang; Xiaofeng Luo (Environmental Development, 2026)

ACSL4 Inhibition by AS-252424 Protects Visual Function by Suppressing RGC Ferroptosis After Retinal Ischemia Reperfusion Injury - Keyu Liu; Zihao Lin; Wu Xiang; Jiayi Zhang; Xiaofeng Wu; Chenzhao Ma; Yantao Wei; Jiawei Wang; Jianqiao Li (Molecular Neurobiology, 2026)

Differential life cycle toxic effects and molecular mechanisms of Di(2-ethylhexyl) phthalate (DEHP) exposure on the female reproductive system - Kangshuai Zhang; Yuxuan Lin; Xiance Sun; Cong Zhang; Haoyuan Deng; Xiaofeng Yao; Ningning Wang; Guang Yang (Toxicology, 2025)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Product and mechanistic insights into the oxidation of cyclohexane via synchrotron radiation vacuum ultraviolet photoionization mass spectrometry - Xiaoxiao Lin; Lingyu Liu; Yu Xia; Zuoying Wen; Christa Fittschen; Wei Liu; Milán Szőri; Béla Fiser; Zhandong Wang; Xiaofeng Tang (Science of The Total Environment, 2025)

Online characterization of particle size distribution and molecular structure of cigarette smoke aerosols and their exposure risk assessment - Feng Zhao; Jian Wang; Zhen Lei; Zuoying Wen; Jia Wang; Zhandong Wang; Christa Fittschen; Xiaoxiao Lin; Xuejun Gu; Weijun Zhang; Xiaofeng Tang (Journal of Hazardous Materials, 2025)

Mo-Si interfacial layer promoted Pt Mo active sites over ternary Pt-Mo/SiO2 catalyst for efficient water-gas shift reaction - Wenting Zhou; Yuhan Wang; Yongkang Huang; Xiaofeng Gao; Zixuan Ma; Ziyu Song; Lili Lin; Dong Su; Ding Ma; Siyu Yao (Chemical Engineering Journal, 2025)

Product and mechanistic insights into the ozonolysis of Δ3-Carene - Xulian Song; Xiaoxiao Lin; Yu Xia; Ziji Ma; Liqin Jin; Weijun Zhang; Zhandong Wang; Christa Fittschen; Xiaofeng Tang (Atmospheric Environment, 2025)

Improving terrestrial solar-induced chlorophyll fluorescence (SIF) reconstruction through multi-satellite-derived SIF integration: a comparative study in regional scale - Mengting Pan; Xiaofeng Lin; Zhongyong Xiao; Fei Wang; Lifeng Guo; Cuiping Wang; Jinghan Xie; Jingchun Fang (International Journal of Remote Sensing, 2025)

Designation of multi-color and durable antimicrobial lyocell fiber by constructing various structural silver nanoparticles - Xiaofeng Wang; Wanjin Hu; Yonghao Zhou; Mengyao Cai; Xuelin Wang; Ke Lin; Chunhua Zhang; Sijie Zhou; Heng Pan; Lixin Du; Liangjun Xia (Chemical Engineering Journal, 2025)

Alfalfa pan-genome unveiled—a breakthrough in alfalfa genomics-assisted breeding - Gai Huang; Lulu Li; Xiaofeng Cao; Hao Lin (Science China Life Sciences, 2025)

Sedimentary Structure Characteristics and Spatial Distribution Pattern of the Zhaoji Salt Mine Derived from Dense Array Ambient Noise Tomography - Hongwei Wang; Xiaofeng Tian; Qiaoxia Liu; Jia Cheng; Ming Zhou; Zhiping Xu; Jiyan Lin; Shuaipeng Zhu (Journal of Earth Science, 2025)

Coupled Vibration Response Analysis of Tension Leg Platform Tendon Under Irregular Ocean Wave Action - Qiangqiang Wu; Yinguang Du; Xiaofeng Luo; Tao Sun; Heng Lin (Journal of Marine Science and Engineering, 2025)
To analyze the dynamic response of tension leg platform (TLP) tendons under irregular ocean wave action, the governing equations of coupled vibration between the platform and tendon under irregular wave action are established based on Hamilton’s principle and the Kirchhoff hypothesis. Using the spectrum representation–random function method, the power spectral density function of the irregular wave load is derived, and the lateral wave forces at different tendon locations are calculated. The coupled lateral and axial responses of the tendon system are obtained through the fourth-order Runge–Kutta method. Considering the parametric vibrations of both the platform and tendon, the extreme lateral deflection of the tendon is employed as the control index to derive the probability density curves of the tendon deflection under irregular wave load. The results show that the amplitude of the wave load increases gradually along the height of the tendon, with a faster growth rate at locations closer to the water surface. The tendon’s lateral deflection response changes more drastically due to coupled parametric vibration of the platform. Based on 628 complete samples of irregular wave loads, the probability density curve and cumulative distribution curve of the extreme lateral deflection of the tendon under irregular wave loads are obtained. Under typical sea state conditions generated from the P-M wave spectrum, the reliability of the tendon under irregular wave load increases with the initial tension force.

Cadmium and rising tides: Amplified greenhouse gas emissions from mangrove sediment - Hengzhi Yin; Ruili Li; Xiaofeng Wu; Yuefei Huang; Guanghui Lin; Bing Li; Guanqian Wang (Regional Studies in Marine Science, 2025)

Atomically dispersed noble metal-Ox sites for electrocatalytic chlorine evolution - Chen Chen; Baoyi Guo; Tingting Liu; Ruting Lin; Yuyu Liu; Qiufeng Huang; Xiaofeng Zhang; Jiabao Huang; Fangren Qian; Shengyun Huang; Qingjun Chen; Xueqin Mu; et al. (Chemical Engineering Journal, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Evolutionary dynamics and codon bias analysis of canine circovirus: Insights into global spread and host adaptability - Gen Li; Rongqi Liu; Yongyi Chen; Huixian Liang; Yinyi Liang; Xin Li; Yankun Ke; Bowen Lin; Jianfeng Zhong; Xiaofeng Guo; Jun Che; Jun Luo (Molecular Phylogenetics and Evolution, 2025)

Per- and polyfluoroalkyl substances mixture impairs intestinal barrier function through microbiota-derived 21-deoxycortisol and cortisol metabolism dysregulation - Tingting Lin; Luyang He; Sishuo Liu; Yahui Li; Zhi Huang; Delei Cai; Yiming Wang; Zhe Mo; Yi Zhu; Zhijian Chen; Peiwei Xu; Xiaoming Lou; et al. (Journal of Hazardous Materials, 2025)

Synthesis of Pd/SiO2 catalyst with outstanding ambient-temperature formaldehyde decomposition via NH3 treatment of silica supports - Xiaofeng Liu; Yuqin Lu; Yufeng Chi; Chunxi Lin; Xudong Chen; Qi Qin (Journal of Environmental Sciences, 2025)

Genesis of the South Pit Deposit in Jiama District, Tibet: Constraints from Geology, Geochronology and Amphibole Geochemistry - Pan Tang; Juxing Tang; Bin Lin; Aorigele Zhou; Faqiao Li; Xiang Fang; Jing Qi; Mengdie Wang; Yan Xiong; Yuke Xie; Zhengkun Yang; Xiaofeng Yao (Journal of Earth Science, 2025)

Phosphorus accumulation by seabird nesting changes soil bacterial community and nutrient cycles of a subtropical Island - Dandan Long; Qian Chen; Kexin Zhang; Caiyun Zhang; Jiqiu Li; Hongyou Hu; Xiaofeng Lin (Biology and Fertility of Soils, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Individual differences moderate the effects of basic psychological need satisfaction on nature visit motivation - Xiangwu Cai; Li Lin; Xiaofeng Wu; Qin Yang; Chen Yan (Journal of Environmental Management, 2025)

Aerosol particle effective density of heated tobacco products measured with a tandem mass and mobility analyzer - Xuejun Gu; You Peng; Xiaofeng Tang; Zuoying Wen; Xiaoxiao Lin; Xiangyu Li; Qingyuan Hu; Jian Wang; Weijun Zhang (Journal of Aerosol Science, 2025)

Ultrahigh-efficiency and synchronous removal of microplastics-tetracycline composite pollutants via S-scheme core-shell magnetic nanosphere - Yujie Zhou; Xiaofeng Lin; Xin You; Ni Xue; Zilong Liu; Yanpeng Cai (Environmental Pollution, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Combining metabolomics to analyze the effects of cell wall component and stone cells on fruit texture in Dangshan pear - Pengcheng Wei; Xianang Wu; Xiaofeng Feng; Ping Lu; Yongping Cai; Lianping Wei; Lin Liu (Horticulture, Environment, and Biotechnology, 2025)

High-pressure Raman spectroscopy of Al-rich and pure-Mg phase D - Chaowen Xu; Li Zhang; Xiaofeng Lu; Yanhao Lin; Shuo Qu; Shuchang Gao; Fengxia Sun; Ying Li (Physics and Chemistry of Minerals, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Spatio-Temporal Dynamics of Particulate Organic Carbon and Its Response to Climate Change: Evidence of the East China Sea from 2003 to 2022 - Zhenghan Liu; Yingfeng Chen; Xiaofeng Lin; Wei Yang (Journal of Marine Science and Engineering, 2025)
Particulate organic carbon (POC) plays a crucial role in oceanic climate change. However, existing research is limited by several factors, including the scarcity of long-term data, extensive datasets, and a comprehensive understanding of POC dynamics. This study utilizes monthly average POC remote sensing data from the MODIS/AQUA satellite to analyze the spatiotemporal variations of POC in the East China Sea from 2003 to 2022. Employing correlation analysis, spatial autocorrelation models, and the Geodetector model, we explore responses to key influencing factors such as climatic elements. The results indicate that POC concentrations are higher in the western nearshore areas and lower in the eastern offshore regions of the East China Sea (ECS). Additionally, concentrations are observed to be lower in southern regions compared to northern ones. From 2003 to 2022, POC concentrations exhibited a fluctuating downward trend with an average annual concentration of 121.05 ± 4.57 mg/m3. Seasonally, monthly average POC concentrations ranged from 105.48 mg/m3 to 158.36 mg/m3; notably higher concentrations were recorded during spring while summer showed comparatively lower levels. Specifically, POC concentrations peaked in April before rapidly declining from May to June—reaching a minimum—and then gradually increasing again from June through December. Correlation analysis revealed significant influences on POC levels by particulate inorganic carbon (PIC), sea surface temperature (SST), chlorophyll (Chl), and photosynthetically active radiation (PAR). The Geodetector model further elucidated that these factors vary in their impact: Chl was identified as having the strongest influence (q = 0.84), followed by PIC (q = 0.75) and SST (q = 0.64) as primary influencing factors; PAR was recognized as a secondary factor with q = 0.30. This study provides new insights into marine carbon cycling dynamics within the context of climate change.

Distribution of phthalic acid esters in propolis ethanolic extract and capsuled propolis - Rifat Nowshin Raka; Haitao Xu; Meichao Bu; Lin Zhang; Xiaofeng Xue (Food Additives & Contaminants: Part A, 2025)

Integration of microbiomics and metabolomics reveals energy metabolism imbalance in crucian carp (Carassius auratus) under saline-alkaline exposure - Lin Han; Wenzhi Liu; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Mechanism of blocking the glutamate pathway to exacerbate oxidative stress, ammonia toxicity and metabolic disorders in crucian carp (Carassius auratus) under saline-alkaline exposure - Wenzhi Liu; Lin Han; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Methamphetamine and HIV-1 Tat Protein Synergistically Induce Endoplasmic Reticulum Stress to Promote TRIM13-Mediated Neuronal Autophagy - Chan Wang; Genmeng Yang; Jian Huang; Yunqing Tian; Chi-Kwan Leung; Lin Miao; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Liu Liu; Juan Li; et al. (Molecular Neurobiology, 2025)

Decipher syntrophies and adaptive response towards enhancing conversion of propionate to methane under psychrophilic condition - Miao Yan; Zhijian Shi; Xinjie Zhang; Xiaofeng Lin; Yongming Sun; Xingyu Cheng; Hailin Tian; Ying Li (Water Research, 2025)

Study on the moisture adsorption characteristics of AlPO4-LTA and its dehumidification performance in desiccant coated dehumidifier - Yaofeng Zhang; Lin Liu; Peng Liu; Lisheng Deng; Jun Li; Xiaofeng Guo; Yugo Osaka; Hongyu Huang (International Journal of Refrigeration, 2025)

Influence of polishing ratio on the rice brewing characteristics and the flavour quality of sake - Zifei Zhao; Yafeng Ding; Xiaofeng Zhang; Xinxia Zhang; Ting Li; Qinlu Lin; Li Wang (Food Bioscience, 2025)

The Role and Mechanism of TRIM13 Regulation of TRAF6 Ubiquitination in the Synergy of Inflammatory Responses and Neurotoxicity Induced by METH and HIV- 1 Tat Protein in Astrocytes - Yi Tan; Lin Miao; Chan Wang; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Yunqing Tian; Genmeng Yang; Xiaofeng Zeng; Juan Li (Neurotoxicity Research, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

In situ restoration of river sediment by sediment microbial fuel cells enhanced with ecological floating islands - Xiao Li; Jiarui Qi; Jinfeng Zhang; Qinghe Zhang; Qichen Lin; Xiaofeng Li; Jianjun Yu (Journal of Soils and Sediments, 2025)

Genome-wide identification, characterization, and expression analysis of the gibberellin-20-oxidase gene family in Artemisia annua L. - Ying Meng; Lin Cai; Dongrui Liang; Mengzhu Cao; Yan Yan; Lanhua Peng; Wenrui He; Xiaofeng Shen (Genetic Resources and Crop Evolution, 2025)

Mitochondrial mechanism of florfenicol-induced nonalcoholic fatty liver disease in zebrafish using multi-omics technology - Lin Zhang; Yang Du; Yameng Li; Tiancai Wang; Yecan Pan; Xiaofeng Xue; Xiyan Mu; Jing Qiu; Yongzhong Qian (Journal of Hazardous Materials, 2025)

Potential ecological risk of microplastics contamination to environment in protect area lakes - Li Naying; Mei Xintong; Zhong Bo; Wang Xiaofeng; Liu Xin; Yang zao; Lin Honghui; He Yixin (Journal of Hazardous Materials, 2025)

A novel ratiometric electrochemical aptasensor based on graphene quantum dots/Cu-MOF nanocomposite for the on-site determination of Staphylococcus aureus - Xiaofeng Lin; Chenghao Liu; Qiaowen Lei; Xinru Nan; Yunxiao Zhu; Jing Liao; Zhizhi Du; Chenyi Ye; Yixian Xiong; Min Yang; Xiaojun Fang; Yan Luo; et al. (Journal of Hazardous Materials, 2025)

Efficient and stable extraction of nano-sized plastic particles enabled by bio-inspired magnetic “robots” in water - Yanpeng Cai; Buyun Zheng; Xiaofeng Lin; Xin You; Qunpo Jia; Ni Xue (Environmental Pollution, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

Why do rice farmers reuse pesticides after purchasing regional pest control services? - Lin Tang; Xiaofeng Luo; Sanxia Du; Yanzhong Huang; Yurong Yang (Environment, Development and Sustainability, 2025)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

Construction of C3N4/Ag2S p-n semiconductor heterojunction coupled with Ag-induced SPR effect on CF cloth for improving photocatalytic activity - Qingquan Xue; Kaiwei Hu; Qian Feng; Hao Lin; Minuo Dong; Kashif Hayat; Yang Zhang; Xiaofeng Shen; Shijie Li (Journal of Environmental Chemical Engineering, 2024)

Investigating carbon peak prediction scenarios and implementation strategies in higher education institutions: A case study of Shandong Jianzhu university - Qianmiao Yang; Lan Wang; Ran Huo; Weihua Lin; Xiaofeng Li (Energy and Buildings, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Precise diagnosis of a hereditary spherocytosis patient with complicated hematological phenotype - Guanxia Liang; Zezhang Lin; Yang Zhang; Qianqian Zhang; Dina Zhu; Xiongda Liang; Hongting Xie; Xiaofeng Wei; Xuan Shang (Molecular Genetics and Genomics, 2024)

Biochar modification accelerates soil atrazine biodegradation by altering bacterial communities, degradation-related genes and metabolic pathways - Yijie Chen; Zhen Zhen; Weilong Wu; Changhong Yang; Guiqiong Yang; Xiaofeng Li; Qing Li; Xiaolan Zhong; Junyong Yin; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2024)

Optimizing iodine adsorption in functionalized metal-organic frameworks via an unprecedented positional isomerism strategy - Zi-Jian Li; Juejing Liu; Guangtao Zhang; Chris Benmore; Linjuan Zhang; Xiaofeng Guo; Jian Lin (Chemical Engineering Journal, 2024)

Fluorescent carbon dots based on food wastes: Applications in food safety detection - Chenghao Liu; Yanqiu Mei; Qiaowen Lei; Xiaoming Ma; Xinru Nan; Yunxiao Zhu; Jing Liao; Youhong Xu; Yan Luo; Hanqiang Zhang; Min Yang; Xiaofeng Lin; et al. (Chemical Engineering Journal, 2024)

The oncogenic role of EIF4A3/CDC20 axis in the endometrial cancer - Yan Lin; Lili Kong; Yiting Zhao; Fengguang Zhai; Ziqing Zhan; Yuxuan Li; Zheng Jingfei; Yan Chunhong; Xiaofeng Jin (Journal of Molecular Medicine, 2024)

Effects of different ammonia energy ratio on soot formation and oxidation in an ammonia diesel dual-fuel engine - Xiaofeng Wang; Taifeng Shi; Shouying Jin; Minshuo Shi; Jiewei Lin; Binyang Wu (Science of The Total Environment, 2024)

Enhanced fucoxanthin and biomass accumulation in Phaeodactylum tricornutum by combined effect of two plant hormones - Jiaxue Lin; Shaogeng Zhao; Beichen Huang; Jianhua Yin; Shengjie Li; Yan Ma; Jingrun Ye; Haiying Wang; Xiaofeng Ji; Jiakun Xu; Zhipeng Wang (Food Bioscience, 2024)

Upcycling of Pb from lead smelting residues to lead halide perovskite for piezocatalytic hydrogen production - Xiaofeng Mo; Mengye Wang; Han Song; Jie Li; Zhen Wu; Zhang Lin (Chemical Engineering Journal, 2024)

DNA demethylase Tet2 promotes the terminal maturation of natural killer cells - Yuqing Lin; Biyun Yang; Hailin Liu; Guanghe Ran; Liang Song; Meng Meng; Xiaofeng Yin; Qinghua Bi; Dongmei Yan; Youcai Deng; Yonghui Lu (Immunologic Research, 2024)

Urban mangroves at risk: Understanding organophosphate flame retardant pollution at different urban function zones in shenzhen - Wenjun Zhao; Bing Li; Ruili Li; Xiaofeng Wu; Guanghui Lin; Yuefei Huang (Ocean & Coastal Management, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

A tetrahedral DNA nanostructure-mediated miRNA inhibitor delivery system: Type H vessel-related bone healing during distraction osteogenesis - Weidong Jiang; Shebin Hong; Kai Liu; Lei Qi; Peiqi Zhu; Xiaofeng Wang; Hao Sun; Hao Wu; Jian Cao; Kaili Lin; Xudong Wang (Chemical Engineering Journal, 2024)

Impacts of cation modification on the carrier dynamics and chemical stability of SnO2-based buried interfaces in perovskite solar cells - Jidong Deng; Abduvely Mijit; Xubiao Wang; Yinhu Gao; Yuliang Che; Lu Lin; Xiaofeng Li; Minyi Huang; Li Yang; Jinbao Zhang (Chemical Engineering Journal, 2024)

Ground-based cloud microphysical observations at Mount Lu in the East Asian monsoon region from 2015 to 2020 - Lijun Guo; Jing Duan; Xiaopeng Zhang; Jun Li; Kai Lyu; Yi Chang; Guangxian Lu; Dawei Lin; Tian Luan; Xiaofeng Lou; Baojun Chen (Atmospheric Research, 2024)

Integration of surface-based and space-based atmospheric CO2 measurements for improving carbon flux estimates using a new developed 3-GAS inversion model - Shu'an Liu; Xiaofeng Pan; Xiangyun Xiong; Tianle Sun; Lin Xue; Huifang Zhang; Junjun Fang; Jingchun Fang; Guchun Zhang; Hui Xu; Baozhang Chen (Atmospheric Research, 2024)

Disinfection efficacy of slightly acidic electrolyzed water on microorganisms: Application in contaminated waste sorting rooms across varied scenarios - Yanyan Guo; Kunsen Lin; Xiaofeng Gao; Qiyuan Zheng; Tao Zhou; Youcai Zhao (Journal of Cleaner Production, 2024)

Constructing highly active vanadyl species for efficient selective catalytic reduction of NO - Chunxi Lin; Zhihua Lian; Weidong Huang; Qiang Wang; Hui Zhang; XiaoFeng Liu; Feng Deng; Xiaoyan Shi; Wenpo Shan; Hong He (Journal of Environmental Chemical Engineering, 2024)

Fabrication of PVDF membranes via γ-ray irradiation and investigation into their membrane formation mechanisms and water treatment properties - Weizhi Liu; Yongqiang Guo; Zhiwei Xue; Hao Sun; Xiaofeng Lin; Chao Liu (Chemical Engineering Journal, 2024)

The urgent need to reduce phosphorus discharges for sustainable mangrove wetland management - Lixia Qiu; Enhao Wang; Ruili Li; Xiaofeng Wu; Yuefei Huang; Guanghui Lin; Bing Li (Water Research, 2024)

Soil microorganisms play an important role in the detrimental impact of biodegradable microplastics on plants - Jiaxi Liu; Siqi Han; Peiyuan Wang; Xiaofeng Zhang; Jiuyu Zhang; Lijun Hou; Yiqiong Zhang; Yufan Wang; Li Li; Yanbing Lin (Science of The Total Environment, 2024)

Anthropogenic and biological activities elevate microplastics pollution in headwater ecosystem of Yangtze tributaries in Hindu Kush-Himalayan region - Naying Li; Xiaofeng Wang; Xianxiang Li; Shaoliang Yi; Yun Guo; Ning Wu; Honghui Lin; Bo Zhong; Wei-Min Wu; Yixin He (Journal of Hazardous Materials, 2024)

Taxonomy of Two New Peritrich Ciliates (Protozoa: Ciliophora) from Inland Saltwaters of China - Ying Yu; Yong Zhang; Ziyao Liang; Jiqiu Li; Xiaofeng Lin (Journal of Ocean University of China, 2024)

Optimizing the deployment of LID facilities on a campus-scale and assessing the benefits of comprehensive control in Sponge City - Xianbao Zha; Wei Fang; Wei Zhu; Shuangtao Wang; Yong Mu; Xiaofeng Wang; Pingping Luo; Mohd Remy Rozainy Mohd Arif Zainol; Mohd Hafiz Zawawi; Khai Lin Chong; Apip Apip (Journal of Hydrology, 2024)

Borneol serves as an adjuvant agent to promote the cellular uptake of curcumin for enhancing its photodynamic fungicidal efficacy against Candida albicans - Zhenlong Zhou; Shengli Wang; Penghui Fan; Xiaofeng Meng; Xinyu Cai; Wen Wang; Lin Ma; Hang Ma; Jianyu Su (Journal of Photochemistry and Photobiology B: Biology, 2024)

3D Models of Sarcomas: The Next-generation Tool for Personalized Medicine - Ruiling Xu; Ruiqi Chen; Chao Tu; Xiaofeng Gong; Zhongyue Liu; Lin Mei; Xiaolei Ren; Zhihong Li (Phenomics, 2024)

Microscopic insights into acid corrosion effects on chelated MSW incineration fly ash: Mechanisms of chelate destabilization - Jinyuan Lin; Xiaofeng Gao; Deli Wu; Bo Yang; Hongping He; Xunchang Fei (Journal of Cleaner Production, 2024)

Numerical simulation of hydrothermal flow in the North China Plain: A case study of Henan Province - Xiaofeng Jia; Yunhong Lin; Maolin Ouyang; Xiaorui Wang; Hongming He (Geothermics, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Does internet use promote clean energy use for cooking by women-headed rural households in China? - Aqian Yan; Xiaofeng Luo; Junbiao Zhang; Lin Tang (Utilities Policy, 2024)

Intramolecular carbon isotopic rollover in propane from natural gas reservoirs of the Santanghu Basin: Insights into chemical structure of kerogen - Peng Liu; Xiaofeng Wang; Changjie Liu; Ying Lin; Ruiliang Guo; Wenhui Liu (Organic Geochemistry, 2024)

Rare earth dissolution from polishing powder waste in H2O2-H2SO4 system: Condition optimization and leaching mechanism - Lin Chen; Xiaofeng He; Xiaona Dang; Xingcang Wang; Weifeng Liu; Duchao Zhang; Tianzu Yang (Hydrometallurgy, 2024)

How antibiotic exposure affect predator-prey interactions by population dynamics in ciliates? - Jiqiu Li; Ziyue Yu; Qinyun Zheng; Weihuang Chen; Xiaofeng Lin (Aquatic Toxicology, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Wide-swath and high-resolution whisk-broom imaging and on-orbit performance of SDGSAT-1 thermal infrared spectrometer - Zhuoyue Hu; Xiaoyan Li; Liyuan Li; Xiaofeng Su; Lin Yang; Yong Zhang; Xingjian Hu; Chun Lin; Yujun Tang; Jian Hao; Xiaojin Sun; Fansheng Chen (Remote Sensing of Environment, 2024)

Efficient processing rare earth polishing powder solid waste by thiourea-H2SO4 system: Process optimization and thiourea decomposition effect - Chen Lin; Chen Wenjie; He xiaofeng; Zhang Duchao; Liu Weifeng; Yang Tianzu (Process Safety and Environmental Protection, 2024)

Effects of salinity in food waste on the growth of black soldier fly larvae and global warming potential analysis - Rui Li; TianHui Lin; XiaoLei Fan; XiaoFeng Dai; JieHua Huang; YiFeng Zhang; RongBo Guo; ShanFei Fu (Chemical Engineering Journal, 2024)

Fragmentation of continental subduction is ending the Himalayan orogeny - Xiaofeng Liang; Yang Chu; Bo Wan; Ling Chen; Lin Chen; Eric Sandvol; Stephen P. Grand; Yibing Li; Minling Wang; Xiaobo Tian; Yun Chen; Tao Xu; et al. (Science Bulletin, 2023)

Microbial mechanism of biochar addition to reduce N2O emissions from soilless substrate systems - Xiaofeng Liang; Wanlai Zhou; Rui Yang; Dongdong Zhang; Hong Wang; Qiaozhen Li; Zhiyong Qi; Yuzhong Li; Wei Lin (Journal of Environmental Management, 2023)

Cannabidiol protects the liver from α-Amanitin-induced apoptosis and oxidative stress through the regulation of Nrf2 - Haowei Wang; Genmeng Yang; Xiaoxing Zhang; Huijie Zhang; Yan Liu; Chan Wang; Lin Miao; Yi Li; Yizhen Huang; Hanxin Teng; Shangwen Wang; Hao Cheng; et al. (Food and Chemical Toxicology, 2023)

MoS2 functionalized lithium complex soap with enhanced thickening net structure toward high-performance thickener - Xiaoqiang Fan; Xiaofeng Wei; Yushan He; Zhuang Zhao; Kaiyue Lin; Minhao Zhu (Chemical Engineering Journal, 2023)

Does it matter who spreads and to which farmers? The influence of video extension on Chinese farmers’ green control technology adoption behavior - Sanxia Du; Xiaofeng Luo; Lin Tang; Yanzhong Huang; Aqian Yan (Environment, Development and Sustainability, 2023)

Circumstellar material ejected violently by a massive star immediately before its death - Jujia Zhang; Han Lin; Xiaofeng Wang; Zeyi Zhao; Liping Li; Jialian Liu; Shengyu Yan; Danfeng Xiang; Huijuan Wang; Jinming Bai (Science Bulletin, 2023)

The R2R3-MYB transcription factor CsMYB42 regulates theanine biosynthesis in albino tea leaves - Nianci Xie; Xiangxiang Huang; Jiaxin Zhou; Xiaofeng Song; Junming Lin; Meihong Yan; Mingzhi Zhu; Juan Li; Kunbo Wang (Plant Science, 2023)

Numerical signal calculation and detection capability of magnetic resonance antenna with high rectangular coefficient - Jun Lin; Yong Sun; Hao Ding; Pengyu Wang; Kaihua Lu; Xiaofeng Yi (Journal of Applied Geophysics, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

High-strength, self-reinforcing and recyclable multifunctional lignin-based polyurethanes based on multi-level dynamic cross-linking - Zhiyi Huang; Huan Wang; Jiahao Du; Xiaochun Liu; Guoyi Pan; Xingshan Yin; Wenjing Lin; Xiaofeng Lin; Yingjuan Sun; Guobin Yi; Li Niu (Chemical Engineering Journal, 2023)

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

Skeleton engineering of rigid covalent organic frameworks to alter the number of binding sites for improved radionuclide extraction - Xiangbin Lin; Weiwen Xin; Shusen Chen; Yan Song; Linsen Yang; Yongchao Qian; Lin Fu; Yanglansen Cui; Xiaofeng He; Tinyang Li; Zhehua Zhang; Yadong Wu; et al. (Journal of Hazardous Materials, 2023)

Characterization of the vertical evolution of urban nocturnal boundary layer by UAV measurements: Insights into relations to cloud radiative effect - Lin Shen; Jiaoshi Zhang; Yin Cheng; Xiaofeng Lu; Haosheng Dai; Dexia Wu; Da-Ren Chen; Jianguo Liu; Huaqiao Gui (Environmental Research, 2023)

Interactions between arsenic migration and CH4 emission in a soil bioelectrochemical system under the effect of zero-valent iron - Zhenyue Lin; Liuying Wang; Mingyu Luo; Xiaofeng Yi; Jianming Chen; Yuanpeng Wang (Chemosphere, 2023)

A rapid approach to evaluating ground surface conditions for shale gas extraction in mountainous areas - Xiaofeng Xu; Wanzhong Shi; Xinyu Zhang; Jianwei Lin; Wanjun Lu; Qian Feng; Xianglin Chen; Ren Wang; Xiaoming Zhang (Gas Science and Engineering, 2023)

Insights into the interfacial structure of Cu/ZrO2 catalysts for methanol synthesis from CO2 hydrogenation: Effects of Cu-supported nano-ZrO2 inverse interface - Yangzhi Xu; Maolin Wang; Zhiwei Xie; Dong Tian; Guan Sheng; Xin Tang; Haibo Li; Yichao Wu; Chuqiao Song; Xiaofeng Gao; Siyu Yao; Ding Ma; et al. (Chemical Engineering Journal, 2023)

Applying machine learning to fine classify construction and demolition waste based on deep residual network and knowledge transfer - Kunsen Lin; Youcai Zhao; Tingting Zhou; Xiaofeng Gao; Chunbo Zhang; Beijia Huang; Qinyan Shi (Environment, Development and Sustainability, 2023)

α-amanitin induces autophagy through AMPK-mTOR-ULK1 signaling pathway in hepatocytes - Yue Xu; Shangwen Wang; Chi-Kwan Leung; Hao Chen; Chan Wang; Huijie Zhang; Shuwei Zhang; Yi Tan; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Toxicology Letters, 2023)

Nanoengineering multifunctional extracellular vesicles availably mitigate bone loss in osteoporosis through binding to RANKL and rebalancing the Treg/Th17 cells - Zhengyu Yang; Zhen Yang; Lin Ding; Cong Liu; Fujian Zhao; Xiaofeng Chen; Chang Du (Chemical Engineering Journal, 2023)

Upcycling of nickel iron slags to hierarchical self-assembled flower-like photocatalysts for highly efficient degradation of high-concentration tetracycline - Zhen Wu; Mengye Wang; Yang Bai; Han Song; Jiaxin Lv; Xiaofeng Mo; Xiaoqin Li; Zhang Lin (Chemical Engineering Journal, 2023)

Potential determinants affecting the growth of China’s ocean economy: An input-output structural decomposition analysis - Li Zheng; Hongyang Zou; Xiaofeng Duan; Zhongguo Lin; Huibin Du (Marine Policy, 2023)

Research and demonstration on reclaimation of chemical industrial wastewater with high salinity and hardness and purification of reverse osmosis concentrates - Mu Liu; Zehua Li; Mengyuan Duan; Yingqiang Su; Xiaofeng Lin; Huiming Han; Kai Sun (Desalination, 2023)

An overview of 2D metal sulfides and carbides as Na host materials for Na-ion batteries - Javed Rehman; Shiru Lin; Mehwish K. Butt; Xiaofeng Fan; Tamer Khattab; Khaled A. Elsayed; Mohamed F. Shibl (Chemical Engineering Journal, 2023)

Can smartphone use increase farmers’ willingness to participate in the centralized treatment of rural domestic sewage? Evidence from rural China - Lin Tang; Xiaofeng Luo; Yanzhong Huang; Sanxia Du; Aqian Yan (Environment, Development and Sustainability, 2023)

m6A writer WTAP targets NRF2 to accelerate bladder cancer malignancy via m6A-dependent ferroptosis regulation - Ke Wang; Gang Wang; Gang Li; Wei Zhang; Yarong Wang; Xiaofeng Lin; Chengxian Han; Hanxuan Chen; Liang Shi; Abudoula Reheman; Jingkai Li; Zhaomin Li; et al. (Apoptosis, 2023)

Energy metabolism response induced by microplastic for marine dinoflagellate Karenia mikimotoi - Ting Zhao; Liju Tan; Xiaotian Han; Xiaofeng Ma; Kun Lin; Jiangtao Wang (Science of The Total Environment, 2023)

Non-destructive determination of internal defects in chestnut (Castanea mollissima) during postharvest storage using X-ray computed tomography - Jiahua Wang; Zelin Lu; Xiaofeng Xiao; Mengting Xu; Yuqing Lin; Huang Dai; Xiaodan Liu; Fuwei Pi; Donghai Han (Postharvest Biology and Technology, 2023)

Microbial deposition and growth on polyamide reverse osmosis membrane surfaces: Mechanisms, impacts, and potential cures - Hongbin Li; Yongqiang Guo; Chao Liu; Yi Zhou; Xiaofeng Lin; Fei Gao (Desalination, 2023)

Source of Ore-Forming Fluid and Material in the Baiyun Gold Deposit, Liaoning Province, NE China: Constraints from H-O-S-Pb Isotopes and in-situ Analyses of Au-Bearing Pyrites - Chenggui Lin; Xiaofeng Yao; Jingwen Mao; Tingjie Yan; Zhizhong Cheng; Kuifeng Mi; Hongxiang Jia; Lujun Lin (Journal of Earth Science, 2023)

Efficient removal of Sb(III) from water using β-FeOOH-modified biochar:Synthesis, performance and mechanism - Ling Lai; Xitao Liu; Wenbo Ren; Zhou Zhou; Xiwang Zhao; Xiaofeng Zeng; Chunye Lin; Mengchang He; Wei Ouyang (Chemosphere, 2023)

Catalytic co-cracking of biomass and waste plastics with sawdust mediated ZSM-5 synthesized via activating gel process - Fuwei Li; Xiaofeng Wang; Hengshuo Gu; Hongbing Fu; Asad Ali; Hongfei Lin; Zhixia Li (Fuel, 2023)

Coordination-enhanced extraction of rare earth metals from waste polishing powder and facile preparation of a mesoporous Ce-La oxide - Xiaofeng He; Lin Chen; Peng Chen; Weifeng Liu; Duchao Zhang; Tianzu Yang (Chemical Engineering Journal, 2023)

Multi-responsive graphene quantum dots hybrid self-healing structural color hydrogel for information encoding and encryption - Jingye Yan; Guoyi Pan; Wenjing Lin; Zilun Tang; Jieheng Zhang; Jiaxin Li; Wenping Li; Xiaofeng Lin; Hongsheng Luo; Guobin Yi (Chemical Engineering Journal, 2023)

Rapid detection and identification of fungi in grain crops using colloidal Au nanoparticles based on surface-enhanced Raman scattering and multivariate statistical analysis - Huiqin Wang; Mengjia Liu; Huimin Zhao; Xiaofeng Ren; Taifeng Lin; Ping Zhang; Dawei Zheng (World Journal of Microbiology and Biotechnology, 2023)

Spatio-temporal association mining of intercity PM2.5 pollution: Hubei Province in China as an example - Jiangping Chen; Xiaofeng Song; Lin Zang; Feiyue Mao; Jianhua Yin; Yi Zhang (Environmental Science and Pollution Research, 2023)

Associations between gastrointestinal infection and urinary phthalate metabolite concentrations in US children and adolescents from NHANES 2005–2016 - Chuang Zhang; Weirui Ren; Chi Sun; Lin Liu; Meng Li; Wenbo Wang; Yanbin Fang; Lin Liu; Xiaofeng Yang; Xiangjian Zhang; Suolin Li (Environmental Science and Pollution Research, 2023)

Applying a deep residual network coupling with transfer learning for recyclable waste sorting - Kunsen Lin; Youcai Zhao; Xiaofeng Gao; Meilan Zhang; Chunlong Zhao; Lu Peng; Qian Zhang; Tao Zhou (Environmental Science and Pollution Research, 2022)

Taxonomy and phylogeny of Pseudovorticella ciliates (Ciliophora, Peritrichia): Two new and one rare species from the coastal waters of China - Yong Zhang; Ying Yu; Zhishuai Qu; Mengmeng Jiang; Zhuo Shen; Jiqiu Li; Xiaofeng Lin (Frontiers in Marine Science, 2022)
Peritrich ciliates are a species-rich group of sessile unicellular eukaryotes, which can be found in various aquatic habitats from all over the world. It is well accepted that there are still many ciliates to be uncovered. During a survey on ciliate biodiversity in the coastal waters of China, three solitary peritrich species were identified as members of the genus Pseudovorticella Foissner & Schiffmann, 1975, including two new species and a rare one. Pseudovorticella zhejiangensis sp. n. differs from its congeners mainly by having a conical-shaped zooid, conspicuous pellicular blisters, one ventral and one dorsal contractile vacuoles, and an infundibular polykinety 3 with three rows of nearly equal length but different beginning positions. Pseudovorticella dalianensis sp. n. can be defined mainly by an obovoid-shaped zooid, one ventral contractile vacuole, and a three-rowed infundibular polykinety 3 with the middle row being the longest. The rare species, Pseudovorticella verrucosa (Dons, 1915) Sun et al., 2009, was redescribed. The small subunit (SSU) rDNA sequences of these three species were sequenced for the first time, the phylogeny of Pseudovorticella species was analyzed, and the results verified the non-monophyly of this genus. This study demonstrates that the morphologic and gene barcoding data are the optimum combination to disclose the biodiversity of ciliates.

Multi-omics analysis on seasonal variations of the biofilm microbial community in a full-scale pre-denitrification biofilter - Lu Tian; Lin Wang; Xiaofeng Zhang; Xuda Huang; Fuhao Wang; Sifu Zhu; Xueqiang Li; Ying Guan (Environmental Science and Pollution Research, 2022)

Transcriptome and metabolome profiling of interspecific CSSLs reveals general and specific mechanisms of drought resistance in cotton - Bei Han; Fengjiao Wang; Zhilin Liu; Lin Chen; Dandan Yue; Weinan Sun; Zhongxu Lin; Xianlong Zhang; Xiaofeng Zhou; Xiyan Yang (Theoretical and Applied Genetics, 2022)

Kelch-like protein 3 in human disease and therapy - Yan Lin; Qian Li; Xiaofeng Jin (Molecular Biology Reports, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Circular RNA circMTO1 suppressed the progression of renal cell carcinoma progression by sponging miR-211 and miR-204 - Ke Wang; Xiaofeng Lin (Mammalian Genome, 2022)

Progranulin Promotes Functional Recovery in Rats with Acute Spinal Cord Injury via Autophagy-Induced Anti-inflammatory Microglial Polarization - Qiang Shi; Yinghao Wu; Baokun Zhang; Shengting Wu; Xin Wang; Fangqi Lin; Guowang Zhang; Xiaofeng Lian; Jianguang Xu (Molecular Neurobiology, 2022)

Inhibition of endoplasmic reticulum stress by 4-phenylbutyrate alleviates retinal inflammation and the apoptosis of retinal ganglion cells after ocular alkali burn in mice - Yanqiao Huang; Miner Yuan; Fang Duan; Yao Yang; Bingsheng Lou; Xiaofeng Lin (Inflammation Research, 2022)

Ore-forming age and tectonic setting of the Linjiasandaogou gold deposit in the Liaodong Peninsula, northeast China: constraints from geochronology and geochemistry - Xiaofeng Yao; Tingjie Yan; Zhicheng Lü; Chenggui Lin; Kuifeng Mi; Shenghui Li; Yang Li; Wange Du (Acta Geochimica, 2022)

Taxonomy and Phylogeny of Two Tintinnid Ciliates of Leprotintinnus (Protista, Ciliophora, Choreotrichida) Combining the Loricae, Cytological, Ontogenetic Features, and Barcoding Genes - Tao Hu; Zhaoyi Wang; Weiwei Liu; Xiaofeng Lin (Frontiers in Marine Science, 2022)
Tintinnid ciliates are a highly diverse and essential group in the marine planktonic microbial loop. However, most of the known tintinnids were recorded only by the lorica characters and very few of them had been studied on their cytological features. In this study, the morphological characters of the lorica, ciliary pattern, nuclear apparatus, ontogenesis, and the molecular phylogeny of two poorly known tintinnid ciliates, Leprotintinnus nordqvisti ( Brandt, 1906 ) Kofoid and Campbell (1929) and L. simplex Schmidt (1902) , isolated from coastal waters of southern China, were investigated based on living observation, silver staining, three nuclear ribosomal DNA markers (18S, ITS1-5.8S-ITS2, and 28S genes) and one mitochondrial DNA marker ( CO1 gene). For the first time, the somatic ciliary pattern of the genus Leprotintinnus was disclosed, viz ., comprising a ventral, a dorsal, and a posterior kinety as well as a right, a left, and a lateral ciliary field. The diagnoses of both Leprotintinnus species were improved and the neotype was assigned. The ontogenesis of L. nordqvisti was in enantiotropic division mode with the new dorsal and posterior kineties generated de novo . The molecular phylogeny confirmed that Leprotintinnus species are closely related to some species of Tintinnopsis , Stylicauda , Rhizodomus , and Climacocylis . The anterior extending of the ventral kinety together with some of the lateral kinety is likely to be a distinguishing feature to determine their systematic relationships. This study also revealed that (i) the lorica of L. nordqvisti is polymorphic or plastic; (ii) Leprotintinnus tubulosus Roxas (1941) might be a synonym of L . nordqvisti ; (iii) Leprotintinnus neriticus sensu Yoo et al. (1988) might be a misidentification of L. simplex .

Taxonomy and systematics of a new pleurostomatid ciliate, Pseudolitonotus spirelis gen. et sp. n. (Protozoa, Ciliophora, Haptoria) - Lei Wu; Jiqiu Li; Alan Warren; Xiaofeng Lin (Marine Life Science & Technology, 2022)

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

Numerical and experimental studies of turbulence in vegetated open-channel flows - Xiaochun Tang; Pengzhi Lin; Philip L.-F. Liu; Xiaofeng Zhang (Environmental Fluid Mechanics, 2021)

Ambient climate determines the directional trend of community stability under warming and grazing - Peipei Liu; Wangwang Lv; Jianping Sun; Caiyun Luo; Zhenhua Zhang; Xiaoxue Zhu; Xingwu Lin; Jichuang Duan; Guangping Xu; Xiaofeng Chang; Yigang Hu; Qiaoyan Lin; et al. (Global Change Biology, 2021)
Changes in ecological processes over time in ambient treatments are often larger than the responses to manipulative treatments in climate change experiments. However, the impacts of human‐driven environmental changes on the stability of natural grasslands have been typically assessed by comparing differences between manipulative plots and reference plots. Little is known about whether or how ambient climate regulates the effects of manipulative treatments and their underlying mechanisms. We collected two datasets, one a 36‐year long‐term observational dataset from 1983 to 2018, and the other a 10‐year manipulative asymmetric warming and grazing experiment using infrared heaters with moderate grazing from 2006 to 2015 in an alpine meadow on the Tibetan Plateau. The 36‐year observational dataset shows that there was a nonlinear response of community stability to ambient temperature with a positive relationship between them due to an increase in ambient temperature in the first 25 years and then a decrease in ambient temperature thereafter. Warming and grazing decreased community stability with experiment duration through an increase in legume cover and a decrease in species asynchrony, which was due to the decreasing background temperature through time during the 10‐year experiment period. Moreover, the temperature sensitivity of community stability was higher under the ambient treatment than under the manipulative treatments. Therefore, our results suggested that ambient climate may control the directional trend of community stability while manipulative treatments may determine the temperature sensitivity of the response of community stability to climate relative to the ambient treatment. Our study emphasizes the importance of the context dependency of the response of community stability to human‐driven environmental changes.

Optimal estimates for dissolved and suspended particulate material fluxes in the Yangtze River, China - Tiantian Yang; Lin Zhang; Yao Yue; Bao Qian; Yuhong Zeng; Xiaofeng Zhang (Environmental Science and Pollution Research, 2021)

Pest control ability, technical guidance, and pesticide overuse: evidence from rice farmers in rural China - Yanzhong Huang; Xiaofeng Luo; Di Liu; Sanxia Du; Aqian Yan; Lin Tang (Environmental Science and Pollution Research, 2021)

Genetic Diversity in Marine Planktonic Ciliates (Alveolata, Ciliophora) Suggests Distinct Geographical Patterns – Data From Chinese and European Coastal Waters - Maximilian H. Ganser; Dominik Forster; Weiwei Liu; Xiaofeng Lin; Thorsten Stoeck; Sabine Agatha (Frontiers in Marine Science, 2021)
Unraveling geographic distribution patterns of planktonic protists is a central goal in marine microbial ecology. Using a novel combination of recently developed phylogenetic and network analyses on a V4 18S rDNA metabarcoding dataset, we here analyzed the genetic diversity of marine planktonic ciliate communities in Chinese and European coastal waters. Thereby, our approach provided an unprecedented perspective on geographic patterns inferred from ciliate genetic diversity and accomplished a very fine resolution down to single nucleotides within operational taxonomic units (OTUs). While most OTUs (87%) exclusively contained sequences of either Chinese or European origin, those OTUs detected in both regions comprised the vast majority of reads (84%). Phylogenetic analyses of OTUs belonging to the same taxon revealed genetically distinct clades that were geographically restricted to either Chinese or European coastal waters. The detection of signature nucleotides emphasized this genetic distinction of Chinese and European clades. Second-level clustering of OTUs and reference sequences in two selected taxa (the oligotrichid Spirotontonia and the tintinnid Tintinnidium ) revealed the presence of several potentially new species or ones lacking genetic reference data. Geographic patterns were also discovered by network analyses within 700 widespread and abundant OTUs; in 77 of these OTUs, European and Chinese sequences formed significantly assortative groups. These assortative groupings indicated a higher genetic similarity among sequences from the same region than between sequences from different regions. Our results demonstrate that detailed analyses of metabarcoding data down to single nucleotide differences expand our perception of geographical distribution patterns and provide insights into historic and ongoing effective dispersal in protists. The congruent discovery of geographic patterns at different levels of resolution (between and within OTUs) suggests that cosmopolitan distribution in marine planktonic ciliates is less common than previously postulated.

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Species Diversity of the Pleurostomatid Ciliate Genus Amphileptus (Ciliophora, Haptoria), With Notes on the Taxonomy and Molecular Phylogeny of Three Species - Lei Wu; Jiqiu Li; Alan Warren; Xiaofeng Lin (Frontiers in Marine Science, 2021)
Amphileptus is one of the largest genera of pleurostomatid ciliates and its species diversity has been reported in various habitats all over the world. In the present work, we review its biodiversity based on data with reliable morphological records. Our work confirms that there are 50 valid Amphileptus species, some of which have a wide range of salinity adaptability and diverse lifestyles. This genus has a high diversity in China but this might be because of the relatively intensive sampling. Phylogenetic analyses based on SSU rDNA sequence data verify the non-monophyly of the genus Amphileptus . Furthermore, two new and one poorly known Amphileptus species, namely A. shenzhenensis sp. n., A. cocous sp. n., and A . multinucleatus Wang, 1934 , from coastal habitats of southern China were investigated using morphological and molecular phylogenetic methods. These three species are highly similar based on their contractile vacuoles and macronuclear nodules. However, they can be discriminated by details of their living morphology and somatic kineties. We also propose two new combinations, Amphileptus polymicronuclei ( Li, 1990 ) comb. n. (original combination Hemiophrys polymicronuclei Li, 1990 ) and Amphileptus salimicus ( Burkovsky, 1970b ) comb. n. (original combination Hemiophrys salimica Burkovsky, 1970b ).

Association of Circulating and Aortic Zinc and Copper Levels with Clinical Abdominal Aortic Aneurysm: a Meta-analysis - Tingting Chen; Hongliang Zhang; Yang Zhang; Mengqi Yang; Juntao Wu; Minjun Yang; Jiangbo Lin; Weixu Gao; Lijiang Tang; Baohui Xu; Jianjun Jiang; Xiaofeng Chen (Biological Trace Element Research, 2021)

Comparative Evaluation on Combined Ecotoxic Effects of Nitrofurazone and NH4CI Using Two Ciliated Protists as Model Organisms: Population Dynamics and Growth Rates - Ziyue Yu; Shuxing Liu; Xin Chen; Alan Warren; Xiaofeng Lin; Jiqiu Li (Journal of Ocean University of China, 2021)

A multi-attribute decision-making model for improving inefficient industrial parks - Sheng-Hau Lin; Danyang Wang; Xianjin Huang; Xiaofeng Zhao; Jing-Chzi Hsieh; Gwo-Hshiung Tzeng; Jia-Hsuan Li; Jia-Tsong Chen (Environment, Development and Sustainability, 2021)

Novel Contributions to the Taxonomy of the Ciliates Genus Euplotes (Ciliophora, Euplotida): Redescription of Two Poorly Known Species, With a Brief Note on the Distributions of This Genus in Coastal Waters of Southern China - Weiwei Liu; Jiamei Jiang; Yehui Tan; Xiaofeng Lin (Frontiers in Marine Science, 2020)
As the typical periphytic ciliate, the genus Euplotes Ehrenberg, 1830 is highly diversified and commonly observed in marine water. In this study, the living morphology, infraciliature and silverline system of two poorly known Euplotes species, E. neapolitanus Wichterman, 1964 and E. antarcticus Fenchel and Lee, 1972 , isolated from coastal water of southern China, were investigated. The original description of these two species were brief, and thus we provided detailed redescription based on our Chinese population. Their diagnoses were improved by adding some morphology characteristics and their detailed illustrations and photomicrographs were first supplied here. Based on the sufficient justification for identification of our population by morphology, their small subunit ribosomal RNA gene sequences which have been reported were linked to the accurate species name. Phylogenetic analyses showed that these two species cluster with their congeners which shared high morphological similarities with them. In addition, the geographic distribution of the genus Euplotes in coast of southern China was revealed, and the mangrove was considered as the ideal habitat for them by possessing the higher species richness.

The spatio-temporal characteristics of aerosol optical thickness as well as the relationship with PM2.5 in Xiamen city, China - Zhongyong Xiao; Xianquan Xie; Xiaofeng Lin; Jinghan Xie; Jiongfeng Chen; Yiqiang Shi; Yingfeng Chen (Environmental Monitoring and Assessment, 2020)

Morphological and physiological variations of Cyclocarya paliurus under different soil water capacities - Ying Feng; Xiulian Lin; Lianwen Qian; Nengjing Hu; Chunfeng Kuang; Xiaofeng Li; Zheng Li; Liangrui Huang; Mingming Liu (Physiology and Molecular Biology of Plants, 2020)

Urban residential land expansion and agglomeration in China: a spatial analysis approach - Xiaofeng Zhao; Mingming Zhang; Ying Li; Xianjin Huang; Baiyuan Wang; Lin Zhang (Environment, Development and Sustainability, 2020)

Taxonomy and Phylogeny of a New Marine Planktonic Ciliate, Strombidium pseudorapulum sp. n. (Protozoa, Ciliophora, Oligotrichia) - Fenfen Li; Yaoyao Huang; Ying Yu; Weiwei Liu; Xiaofeng Lin (Journal of Ocean University of China, 2020)

Characteristics and health risk assessments of heavy metals in PM2.5 in Taiyuan and Yuci college town, China - Xiaofeng Liu; Zhilei Wang; Huiling Bai; Shuting Zhang; Ling Mu; Lin Peng (Air Quality, Atmosphere & Health, 2020)

The power of habit: does production experience lead to pesticide overuse? - Yanzhong Huang; Xiaofeng Luo; Lin Tang; Weizhen Yu (Environmental Science and Pollution Research, 2020)

Ecological risk evaluation and source apportionment of heavy metals in park playgrounds: a case study in Xi’an, Shaanxi Province, a northwest city of China - Bin Guo; Yi Su; Lin Pei; Xiaofeng Wang; Bo Zhang; Dingming Zhang; Xiaoxia Wang (Environmental Science and Pollution Research, 2020)

NLRP3 Deficiency Attenuates Secondary Degeneration of Visual Cortical Neurons Following Optic Nerve Injury - Zhou Zhang; Wenyi Liu; Yubin Huang; Linlin Luo; Xiaofeng Cai; Yunjia Liu; Liqianyu Ai; Jun Yan; Sen Lin; Jian Ye (Neuroscience Bulletin, 2020)

Whole-genome mining and in silico analysis of FAD gene family in Brassica juncea - Yufei Xue; Chengyan Chai; Baojun Chen; Xiaofeng Shi; Bitao Wang; Fanrong Mei; Manlin Jiang; Xueli Liao; Xia Yang; Chenglong Yuan; Lin Zhang; Yourong Chai (Journal of Plant Biochemistry and Biotechnology, 2020)

Overview of the biodiversity and geographic distribution of aloricate oligotrich ciliates (Protozoa, Ciliophora, Spirotrichea) in coastal waters of southern China - Weiwei Liu; Kexin Zhang; Changzhi Chen; Jiqiu Li; Yehui Tan; Alan Warren; Xiaofeng Lin; Weibo Song (Systematics and Biodiversity, 2019)

Effect of soil pH and organic matter content on heavy metals availability in maize (Zea mays L.) rhizospheric soil of non-ferrous metals smelting area - Shengnan Hou; Na Zheng; Lin Tang; Xiaofeng Ji; Yunyang Li (Environmental Monitoring and Assessment, 2019)

G-CSF-primed haplo-identical HSCT with intensive immunosuppressive and myelosuppressive treatments does not increase the risk of pre-engraftment bloodstream infection: a multicenter case–control study - Jinhua Ren; Qiaoxian Lin; Weimin Chen; Congmeng Lin; Yuxin Zhang; Cunrong Chen; Shaozhen Chen; Xiaohong Yuan; Ping Chen; Xiaofeng Luo; Yun Lin; Lvying Shen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Contamination assessment and health risk of arsenic exposure to stairway dust in the zinc smelting district, Northeast China - Na Zheng; Yan Yu; Shengnan Hou; Sujuan Xu; Lin Tang; Xiaofeng Ji (Environmental Geochemistry and Health, 2019)

RACK1 deficiency synergizes with all-trans retinoic acid to induce apoptosis in human acute promyelocytic leukemia cells - Huifang Wu; Jian Liu; Xiaofeng Huang; Lili Pian; Qianqian Cheng; Qingyang Wang; Min Zhao; Zhou Lin; Beifen Shen; Jiyan Zhang; Shulian Li; Jing Wang (Molecular and Cellular Biochemistry, 2019)

Diversity of the cyrtophorid genus Chlamydodon (Protista, Ciliophora): its systematics and geographic distribution, with taxonomic descriptions of three species - Zhishuai Qu; Lifang Li; Xiaofeng Lin; Thorsten Stoeck; Hongbo Pan; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2018)

The AP2/ERF transcription factor CmERF053 of chrysanthemum positively regulates shoot branching, lateral root, and drought tolerance - Jing Nie; Chao Wen; Lin Xi; Suhui Lv; Qingcui Zhao; Yaping Kou; Nan Ma; Liangjun Zhao; Xiaofeng Zhou (Plant Cell Reports, 2018)

Microbial CO2 assimilation is not limited by the decrease in autotrophic bacterial abundance and diversity in eroded watershed - Haibing Xiao; Zhongwu Li; Xiaofeng Chang; Lei Deng; Xiaodong Nie; Chun Liu; Lin Liu; Jieyu Jiang; Jia Chen; Danyang Wang (Biology and Fertility of Soils, 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

New trends in aggregating tags for therapeutic protein purification - Xiaofeng Yang; Marco Pistolozzi; Zhanglin Lin (Biotechnology Letters, 2018)

The cyclin dependent kinase subunit Cks1 is required for infection‐associated development of the rice blast fungus Magnaporthe oryzae - Xiaofeng Yue; Yawei Que; Shuzhen Deng; Lin Xu; Miriam Oses‐Ruiz; Nicholas J. Talbot; Youliang Peng; Zhengyi Wang (Environmental Microbiology, 2017)
Summary Cell cycle regulation is pivotal for proper cell division and cellular differentiation in eukaryotic cells. The central regulators that govern eukaryotic cell cycle progression are cyclin‐dependent kinases (CDKs) and their partners. Here, we report that Magnaporthe oryzae CKS1 encodes a cyclin‐dependent kinase subunit, which plays a significant role in regulation of plant infection. We demonstrate that CKS1 is a functional homolog of CKS1 / SUC1 and can physically interact with the CDK protein Cdc28, and Som1, a downstream regulator of the cyclic AMP‐dependent Protein Kinase A pathway. CKS1 deletion mutants are severely impaired in hyphal growth, sexual reproduction, melanin pigmentation and conidiogenesis. Cks1 mutants are able to form appressoria from hyphal tips, but these are unable to re‐polarize, and rice infection is impaired. CKS1 also affects chitin and glucan synthase activity during cell wall differentiation and fungal hydrophobin function. CKS1 , therefore, encodes a conserved CDK‐binding partner, essential for appressorium‐mediated plant infection by the rice blast fungus.

Development and validation of an ocean wave retrieval algorithm for VV-polarization Sentinel-1 SAR data - Bo Lin; Weizeng Shao; Xiaofeng Li; Huan Li; Xiaoqing Du; Qiyan Ji; Lina Cai (Acta Oceanologica Sinica, 2017)

New taxa refresh the phylogeny and classification of pleurostomatid ciliates (Ciliophora, Litostomatea) - Lei Wu; Xiaoxiao Jiao; Zhuo Shen; Zhenzhen Yi; Jiqiu Li; Alan Warren; Xiaofeng Lin (Zoologica Scripta, 2017)
A high diversity of pleurostomatid ciliates has been discovered in the last decade, and their systematics needs to be improved in the light of new findings concerning their morphology and molecular phylogeny. In this work, a new genus, Protolitonotus gen. n., and two new species, Protolitonotus magnus sp. n. and Protolitonotus longus sp. n., were studied. Furthermore, 19 novel nucleotide sequences of SSU rDNA , LSU rDNA and ITS 1‐5.8S‐ ITS 2 were collected to determine the phylogenetic relationships and systematic positions of the pleurostomatid ciliates in this study. Based on both molecular and morphological data, the results demonstrated that: (i) as disclosed by the sequence analysis of SSU rDNA , LSU rDNA and ITS 1‐5.8S‐ ITS 2, Protolitonotus gen. n. is sister to all other pleurostomatids and thus represents an independent lineage and a separate family, Protolitonotidae fam. n., which is defined by the presence of a semi‐suture formed by the right somatic kineties near the dorsal margin of the body; (ii) the families Litonotidae and Kentrophyllidae are both monophyletic based on both SSU rDNA and LSU rDNA sequences, whereas Amphileptidae are non‐monophyletic in trees inferred from SSU rDNA sequences; and (iii) the genera Loxophyllum and Kentrophyllum are both monophyletic, whereas Litonotus is non‐monophyletic based on SSU rDNA analyses. ITS 1‐5.8S‐ ITS 2 sequence data were used for the phylogenetic analyses of pleurostomatids for the first time; however, species relationships were less well resolved than in the SSU rDNA and LSU rDNA trees. In addition, a major revision to the classification of the order Pleurostomatida is suggested and a key to its families and genera is provided.

Iodine Status of Vulnerable Populations in Henan Province of China 2013–2014 After the Implementation of the New Iodized Salt Standard - Jin Yang; Lin Zhu; Xiaofeng Li; Heming Zheng; Zhe Wang; Yang Liu; Zongyu Hao (Biological Trace Element Research, 2016)

Overexpression of SsDGAT2 from Sapium sebiferum (L.) Roxb Increases Seed Oleic Acid Level in Arabidopsis - YiQiang Wang; Dan Peng; Lin Zhang; XiaoFeng Tan; DeYi Yuan; XuanMing Liu; Bo Zhou (Plant Molecular Biology Reporter, 2016)

Sporogenesis and gametogenesis in Chinese chinquapin (Castanea henryi (Skam) Rehder & Wilson) and their systematic implications - Xiaoming Fan; Deyi Yuan; Jing Tang; Xiaoming Tian; Lin Zhang; Feng Zou; Xiaofeng Tan (Trees, 2015)

Vertical motions of tide gauge stations near the Bohai Sea and Yellow Sea - ShouHua Liu; ChangLin Chen; KeXiu Liu; Lin Mu; Hui Wang; XinRong Wu; JianLi Zhang; XiaoFeng Duan; Jia Gao (Science China Earth Sciences, 2015)

Isolation and purification of rabbit mesenchymal stem cells using an optimized protocol - Chunbo Lin; Maorong Shen; Weiping Chen; Xiaofeng Li; Daoming Luo; Jinhong Cai; Yuan Yang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Characteristics of hopanoid hydrocarbons in ambient PM10 and motor vehicle emissions and coal ash in Taiyuan, China - Feng Han; Junji Cao; Lin Peng; Huiling Bai; Dongmei Hu; Ling Mu; Xiaofeng Liu (Environmental Geochemistry and Health, 2015)

Selenium geochemical distribution in the environment and predicted human daily dietary intake in northeastern Qinghai, China - Dasong Yu; Dongli Liang; Lingming Lei; Rong Zhang; Xiaofeng Sun; Zhiqing Lin (Environmental Science and Pollution Research, 2015)

Molecular phylogenetic lineage of Plagiopogon and Askenasia (Protozoa, Ciliophora) revealed by their gene sequences - An Liu; Zhenzhen Yi; Xiaofeng Lin; Xiaozhong Hu; Saleh A. Al-Farraj; Khaled A. S. Al-Rasheid (Journal of Ocean University of China, 2015)

Recognizing the importance of exposure–dose–response dynamics for ecotoxicity assessment: nitrofurazone-induced antioxidase activity and mRNA expression in model protozoan Euplotes vannus - Yazhen Hong; Shuxing Liu; Xiaofeng Lin; Jiqiu Li; Zhenzhen Yi; Khaled A. S. Al-Rasheid (Environmental Science and Pollution Research, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Taxonomy and molecular phylogeny of four Strombidium species, including description of S. pseudostylifer sp. nov. (Ciliophora, Oligotrichia) - Wen Song; Jiamei Li; Weiwei Liu; Khaled A. S. Al-rasheid; Xiaozhong Hu; Xiaofeng Lin (Systematics and Biodiversity, 2015)

Spatial distribution characteristics of surface tidal currents in the southwest of Taiwan Strait - Zhiben Shen; Xiongbin Wu; Hang Lin; Xiaofeng Chen; Xing’an Xu; Lun Li (Journal of Ocean University of China, 2014)

A Highly Sensitive Solid Substrate Room Temperature Phosphorimetry for Carbaryl Detection Based on its Activating Effect on NaIO4 Oxidizing Fluorescein - Jiaming Liu; Qitong Huang; Zhen-bo Liu; Xiaofeng Lin; Li-Hong Zhang; Chang-Qing Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2014)

CD4+CD25+ regulatory T cells are not required for mesenchymal stem cell function in fully MHC-mismatched mouse cardiac transplantation - Xiaofeng Jiang; Chen Liu; Jianpeng Hao; Dawei Guo; Jinshuai Guo; Junchao Yao; Kun Jiang; Zheming Cui; Lei Zhu; Wenyu Sun; Lin Lin; Jian Liang (Cell and Tissue Research, 2014)

Highly Sensitive Fluorescent Probe for Clenbuterol Hydrochloride Detection Based on its Catalytic Oxidation of Eosine Y by NaIO4 - Jiaming Liu; Zhen-bo Liu; Qitong Huang; Chang-Qing Lin; Xiaofeng Lin (Journal of Fluorescence, 2014)

FGF21 inhibits apolipoprotein(a) expression in HepG2 cells via the FGFR1-ERK1/2-Elk-1 pathway - Xiaolong Lin; Guohua Li; Xinglan He; Xiaofeng Ma; Kai Zhang; Hai Zhang; Gaofeng Zeng; Zuo Wang (Molecular and Cellular Biochemistry, 2014)

Occurrence and particle-size distributions of polycyclic aromatic hydrocarbons in the ambient air of coking plant - Xiaofeng Liu; Lin Peng; Huiling Bai; Ling Mu; Chongfang Song (Environmental Geochemistry and Health, 2014)

The crustal structures of the central Longmenshan along and its margins as related to the seismotectonics of the 2008 Wenchuan Earthquake - ShiXu Jia; BaoJin Liu; ZhaoFan Xu; Zhi Liu; ShaoYing Feng; JianShi Zhang; JieYan Lin; XiaoFeng Tian; QiaoXia Liu; WenBin Guo (Science China Earth Sciences, 2014)

Development of a core set of single-locus SSR markers for allotetraploid rapeseed (Brassica napus L.) - Haitao Li; Muhammad Younas; Xiaofeng Wang; Xuemin Li; Lin Chen; Bo Zhao; Xun Chen; Jinsong Xu; Fan Hou; Baohua Hong; Gang Liu; Hongyang Zhao; et al. (Theoretical and Applied Genetics, 2013)

Transcription factor OsAP21 gene increases salt/drought tolerance in transgenic Arabidopsis thaliana - Xiaofeng Jin; Yong Xue; Ren Wang; RanRan Xu; Lin Bian; Bo Zhu; Hongjuan Han; Rihe Peng; Quanhong Yao (Molecular Biology Reports, 2013)

Molecular characterization of a peritrophic membrane protein from the silkworm, Bombyx mori - Xiaolong Hu; Lin Chen; Rui Yang; Xingwei Xiang; Xiaofeng Wu (Molecular Biology Reports, 2013)

Phylogeny of three choreotrich genera (Protozoa, Ciliophora, Spirotrichea), with morphological, morphogenetic and molecular investigations on three strobilidiid species - Weiwei Liu; Zhenzhen Yi; Xiaofeng Lin; Alan Warren; Weibo Song (Zoologica Scripta, 2012)
Liu, W., Yi, Z., Lin, X., Warren, A. & Song, W. (2012). Phylogeny of three choreotrich genera (Protozoa, Ciliophora, Spirotrichea), with morphological, morphogenetic and molecular investigations on three strobilidiid species. — Zoologica Scripta , 41 , 417–434. The phylogenetic relationships among three strobilidiid genera, namely Strobilidium , Rimostrombidium and Pelagostrobilidium , are investigated using a combination of morphological, morphogenetic and molecular data. The results indicate that all three genera belong to the same lineage, in which Rimostrombidium evolved first and Strobilidium and Pelagostrobilidium derived later. Improved genus diagnoses for Rimostrombidium and Pelagostrobilidium are supplied. The curved kinety 2 and the caudal spiralling of some somatic kineties are confirmed as generic characters for Pelagostrobilidium and Strobilidium , respectively. In addition, the morphology and morphogenesis of three species, namely R. veniliae ( Montagnes & Taylor, 1994 ) Petz et al., 1995 , P. paraepacrum sp. n. and P. minutum sp. n., isolated from the South China Sea are described. Pelagostrobilidium paraepacrum sp. n. is characterized by the presence of six somatic kineties, 30–32 external and two internal membranelles. Pelagostrobilidium minutum sp. n. is characterized by its extremely small body size, four somatic kineties, and in having one internal and 19–21 external membranelles. Rimostrombidium conicum Kahl, 1932 is transferred to the genus Pelagostrobilidium as P. conicum (Kahl, 1932) comb. nov.

Proteomic analysis of peritrophic membrane (PM) from the midgut of fifth-instar larvae, Bombyx mori - Xiaolong Hu; Lin Chen; Xingwei Xiang; Rui Yang; Shaofang Yu; Xiaofeng Wu (Molecular Biology Reports, 2012)

Autographa californica multiple nucleopolyhedrovirus odv-e25 (Ac94) is required for budded virus infectivity and occlusion-derived virus formation - Lin Chen; Xiaolong Hu; Xingwei Xiang; Shaofang Yu; Rui Yang; Xiaofeng Wu (Archives of Virology, 2012)

Extension of the growing season due to delayed autumn over mid and high latitudes in North America during 1982–2006 - Wenquan Zhu; Hanqin Tian; Xiaofeng Xu; Yaozhong Pan; Guangsheng Chen; Wenpeng Lin (Global Ecology and Biogeography, 2012)
Aim We intend to characterize and understand the spatial and temporal patterns of vegetation phenology shifts in North America during the period 1982–2006. Location North America. Methods A piecewise logistic model is used to extract phenological metrics from a time‐series data set of the normalized difference vegetation index (NDVI). An extensive comparison between satellite‐derived phenological metrics and ground‐based phenology observations for 14,179 records of 73 plant species at 802 sites across North America is made to evaluate the information about phenology shifts obtained in this study. Results The spatial pattern of vegetation phenology shows a strong dependence on latitude but a substantial variation along the longitudinal gradient. A delayed dormancy onset date (0.551 days year −1 , P = 0.013) and an extended growing season length (0.683 days year −1 , P = 0.011) are found over the mid and high latitudes in North America during 1982–2006, while no significant trends in greenup onset are observed. The delayed dormancy onset date and extended growing season length are mainly found in the shrubland biome. An extensive validation indicates a strong robustness of the satellite‐derived phenology information. Main conclusions It is the delayed dormancy onset date, rather than an advanced greenup onset date, that has contributed to the prolonged length of the growing season over the mid and high latitudes in North America during recent decades. Shrublands contribute the most to the delayed dormancy onset date and the extended growing season length. This shift of vegetation phenology implies that vegetation activity in North America has been altered by climatic change, which may further affect ecosystem structure and function in the continent.

Oil-Spill Monitoring in the Coastal Waters of Hong Kong and Vicinity - Yuanzhi Zhang; Hui Lin; Qiang Liu; Jinrong Hu; Xiaofeng Li; Kin Yeung (Marine Geodesy, 2012)

Fluid geochemical features and preservation conditions of marine stratum in typical structure of Jianghan plain area - Guosheng Xu; Deyu Gong; Haifeng Yuan; Changhong Li; Guozhi Wang; Xiaofeng Hu; Juanhua Lin; Jianmin Zhu (Journal of Earth Science, 2011)

Taxonomy, morphology and molecular systematics of a new oligotrich ciliate, Williophrya maedai gen. nov., sp. nov., with redescriptions of Strombidium basimorphum and Pseudotontonia simplicidens (Protozoa, Ciliophora, Oligotrichia) - WEIWEI LIU; ZHENZHEN YI; ALAN WARREN; KHALED A. S. AL-RASHEID; SALEH A. AL-FARRAJ; XIAOFENG LIN; WEIBO SONG (Systematics and Biodiversity, 2011)

Satellite altimeter observations of nonlinear Rossby eddy–Kuroshio interaction at the Luzon Strait - Quanan Zheng; Chang-Kuo Tai; Jianyu Hu; Hongyang Lin; Rong-Hua Zhang; Feng-Chun Su; Xiaofeng Yang (Journal of Oceanography, 2011)

Effects of litter quality and climate change along an elevation gradient on litter mass loss in an alpine meadow ecosystem on the Tibetan plateau - Guangping Xu; Yigang Hu; Shiping Wang; Zhenhua Zhang; Xiaofeng Chang; Jichuang Duan; Caiyun Luo; Zengguo Chao; Ailing Su; Qiaoyan Lin; Yingnian Li; Mingyuan Du (Plant Ecology, 2010)

Molecular phylogeny of three ambiguous ciliate genera: Kentrophoros , Trachelolophos and Trachelotractus (Alveolata, Ciliophora) - Shan Gao; Michaela C. Strüder-Kypke; Khaled A. S. Al-Rasheid; Xiaofeng Lin; Weibo Song (Zoologica Scripta, 2010)

Effect of warming and grazing on litter mass loss and temperature sensitivity of litter and dung mass loss on the Tibetan plateau - CAIYUN LUO; GUANGPING XU; ZENGGUO CHAO; SHIPING WANG; XINGWU LIN; YIGANG HU; ZHENHUA ZHANG; JICHUANG DUAN; XIAOFENG CHANG; AILING SU; YINGNIAN LI; XINQUAN ZHAO; et al. (Global Change Biology, 2010)
Knowledge about the role of litter and dung decomposition in nutrient cycling and response to climate change and grazing in alpine ecosystems is still rudimentary. We conducted two separate studies to assess the relative role of warming and grazing on litter mass loss and on the temperature sensitivity of litter and dung mass loss. Experiments were conducted for 1–2 years under a controlled warming–grazing system and along an elevation gradient from 3200 to 3800 m. A free‐air temperature enhancement system (FATE) using infrared heaters and grazing significantly increased soil temperatures (average 0.5–1.6 °C) from 0 to 40 cm depth, but neither warming nor grazing affected soil moisture except early in the growing seasons at 30 cm soil depth. Heaters caused greater soil warming at night‐time compared with daytime, but grazing resulted in greater soil warming during daytime compared with night‐time. Annual average values of the soil temperature at 5 cm were 3.2, 2.4 and 0.3 °C at 3200, 3600 and 3800 m, respectively. Neither warming nor grazing caused changes of litter quality for the first year of the controlled warming–grazing experiment. The effects of warming and grazing on litter mass losses were additive, increasing litter mass losses by about 19.3% and 8.3%, respectively, for the 2‐year decomposition periods. The temperature sensitivity of litter mass losses was approximately 11% °C −1 based on the controlled warming–grazing experiment. The annual cumulative litter mass loss was approximately 2.5 times that of dung along the elevation gradient. However, the temperature sensitivity (about 18% °C −1 ) of the dung mass loss was about three times that of the litter mass loss. These results suggest greater warming at night‐time compared with daytime may accelerate litter mass loss, and grazing will enhance carbon loss to atmosphere in the region through a decrease of litter biomass and an increase of dung production with an increase of stocking rate in future warmer conditions.

Molecular phylogeny of Nothoholosticha (Protozoa, Ciliophora, Urostylida) and systematic relationships of the Holosticha -complex - Zhenzhen Yi; Xiaofeng Lin; Alan Warren; Khaled A. S. Al-Rasheid; Weibo Song (Systematics and Biodiversity, 2010)

Assessment of an analytical model for sea surface wind speed retrieval from spaceborne SAR - Qing Xu; Hui Lin; Xiaofeng Li; Juncheng Zuo; Quanan Zheng; William G. Pichel; Yuguang Liu (International Journal of Remote Sensing, 2010)

Complementary notes on a ‘well-known’ marine heterotrichous ciliate, Folliculinopsis producta (Wright, 1859) Frauré-Fremiet, 1936 (Protozoa, ciliophora) - Daode Ji; Xiaofeng Lin; Weibo Song (Journal of Ocean University of China, 2004)